INCORPORATION OF AU AND AG NANOSTRUCTURES INSIDE SIO2 - Díaz, C.; Valenzuela, A. M. L.; Soto, K.; Laguna-Bercero, M. A. (Journal of the Chilean Chemical Society, 2019)
Incorporation of Au° inside SiO2 was achieved by a solid-state method from the pyrolysis of the composites (Chitosan)•(AuCl3)n•(SiO2)m and (PS-co-4-PVP)•(AuCl3)n•(SiO2)m Similarly, the incorporation of Ag° inside SiO2 it was made from thermal treatment of the composites (Chitosan)•(AgNO3)n•(SiO2)m and (PS-co-4-PVP)•(AgNO3)n•(SiO2)m. The nature of the polymer controls the particle size for the Au/SiO2 composite, while that for the Ag/SiO2 both, polymer Chitosan and PS-co-4-PVP, produces similar particle size. In the case of the composite Ag/SiO2 the particle size as small as 5 nm were obtained. The 1:1 or 1:5 metal/polymer ratios, as well as the nature of the polymer in the macromolecular precursors (Chitosan)•(AuCl3)n•(SiO2)m and (PS-co-4-PVP)•(AuCl3)n•(SiO2)m influences the dispersion of the Au° nanostructures inside SiO2 matrix. The results are compared with those previously obtained for bimetallic composites Au/Ag//SiO2. A formation mechanism of the Au°/SiO2 and Ag°/SiO2 composites involving the combustion of the organic matter and the growth of the Au° and Ag° nanoparticles inside the holes, generated from the combustion process, is proposed.